The Acquisition of Problem Behavior in Individuals With Developmental Disabilities as a Behavioral Cusp. (July 2015) - Robertson, Rachel E.
A behavioral cusp has been defined as a behavior change that produces contact with new contingencies with important and far-reaching consequences. The concept of behavioral cusps has most frequently been used to select target skills taught to learners and to evaluate the importance of those skills; however, the concept is equally applicable to behavior changes that bring about important and far-reaching negative consequences. Although it has been acknowledged that socially undesirable behavior change can also qualify as a behavioral cusp, this area of the cusp concept has been under-examined. In this article, an undesirable behavior change, the acquisition of problem behavior in individuals with developmental disabilities, is compared with criteria for behavioral cusps previously identified in the literature. The advantages of viewing problem behavior as a behavioral cusp are outlined, and implications for practice and research from a behavioral cusp approach to problem behavior are provided.